Interactions between nitric oxide and hydrogen sulfide generating systems in gastric mucosa under condition of the combined action of stress and NDAIDs - Iryna Fomenko, Alexander Sklyarov, Natalia Denysenko, Nazar Hrycevych, Alevtina Dranitsyna, John Wallace (Journal of Applied Pharmaceutical Science, 2017)
The metabolic relationship between H2S and NO in gastric mucosa in norm and pathology is still poorly studied. Aim of this study was to determine mechanisms of interaction between NO and H2S generating systems under conditions of the combined actions of NSAIDs and stress. Water restraint stress (WRS) was used to induce peptic lessions in rats; naproxen and ATB-346 were administered prior to WRS. Nos2, Cbs and Ptgs2 gene expression level was determined by semiquantitative RT-PCR in gastric epitheliocytes. In the gastric mucosa were determined: alterations in H2S and NOx concentrations, changes in activity of myeloperoxidase. Both WRS and naproxen action prior to WRS cased a significant rise in myeloperoxidase activity. Administration of ATB-346 resulted in a considerable decrease of myeloperoxidase activity. Naproxen action caused the downregulation of Nos2. The level of Cbs expression in group pretreated with naproxen was much higher than in group of WRS alone. We suppose that it increases as a result of Nos2 downregulation and the correspondent decrease of NO concentration. The relationship between NO and H2S in the gastric mucosa is likely mediated through the regulation of genes expression. As a result of the released H2S, ATB-346 administration decreased the severity of gastric mucosa lesions.
Keywords: Nitric oxide, hydrogen sulfide, stress, NSADs, gastric mucosa.